Developing economies' participation in environmental services negotiations: What are the challenges and what should be done? - Sanvid Tuljapurkar; Ruosi Zhang (World Trade Organization (WTO), 2023)
The urgency to tackle climate change has placed sustainable development at the centre of recent trade related narratives. With trade being considered as means to achieve sustainable development goals, one issue to be addressed is how to adjust trade negotiations which used to be the main approach to pursuing market opening. In this context, this paper examines trade negotiations on environmental services by focusing on developing economies' participation. Environmental services and related trade play a critical role in achieving environmental and sustainable development goals. Nevertheless, developing economies' participation in environmental services trade negotiations has been limited. By analysing the reasons behind such limited participation and assessing some new approaches, this paper attempts to explore how environmental services trade negotiations could be adapted to better engage developing economies and serve sustainable development goals.
Keywords: F13; F18; F63; 330; Environmental services; developing economies; trade negotiations